2011
DOI: 10.4310/atmp.2011.v15.n4.a5
|View full text |Cite
|
Sign up to set email alerts
|

Null asymptotics of solutions of the Einstein–Maxwell equations in general relativity and gravitational radiation

Abstract: We prove that for spacetimes solving the Einstein-Maxwell (EM) equations, the electromagnetic field contributes at highest order to the nonlinear memory effect of gravitational waves. In [5] Christodoulou showed that gravitational waves have a nonlinear memory. He discussed how this effect can be measured as a permanent displacement of test masses in a laser interferometer gravitational-wave detector. Christodoulou derived a precise formula for this permanent displacement in the Einstein vacuum (EV) case. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 9 publications
(62 reference statements)
4
56
0
Order By: Relevance
“…Thorne [2] and Wiseman and Will [3] soon interpreted Christodoulou's nonlinear memory effect as simply corresponding to the linear memory effect, but with the nonlinear effective stress energy of gravitational waves replacing the "particle" sources. Further support for this interpretation can be found in the fact that a similar nonlinear memory effect occurs when a flux of electromagnetic radiation reaches null infinity [5], thereby showing that the nonlinear memory effect is not special to gravitational waves. Very recently, Bieri and Garfinkle [6] have shown that the linear memory effect for null matter can be derived in close parallel to Christodoulou's derivation, thus further confirming that the nonlinear memory effect can be interpreted as being the same as the linear memory effect, with the effective stress energy of gravitational radiation replacing the ordinary stress energy of null matter.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Thorne [2] and Wiseman and Will [3] soon interpreted Christodoulou's nonlinear memory effect as simply corresponding to the linear memory effect, but with the nonlinear effective stress energy of gravitational waves replacing the "particle" sources. Further support for this interpretation can be found in the fact that a similar nonlinear memory effect occurs when a flux of electromagnetic radiation reaches null infinity [5], thereby showing that the nonlinear memory effect is not special to gravitational waves. Very recently, Bieri and Garfinkle [6] have shown that the linear memory effect for null matter can be derived in close parallel to Christodoulou's derivation, thus further confirming that the nonlinear memory effect can be interpreted as being the same as the linear memory effect, with the effective stress energy of gravitational radiation replacing the ordinary stress energy of null matter.…”
Section: Introductionmentioning
confidence: 89%
“…Consider, in Newtonian gravity, a particle of mass E traveling with velocity c along the z axis. The Newtonian potential produced by such a particle at time t is 5 In particular, the Ricci component R 00 is easily computed by adding together the first two lines of their Eq. (3.12) and does not agree with the (correct) expression they give below Eq.…”
Section: Linearized Gravitational Fieldmentioning
confidence: 99%
“…Gravitational wave memory, a permanent displacement of the gravitational wave detector after the wave has passed, has been known since the work of Zel'dovich and Polnarev [1], extended to the full nonlinear theory of general relativity by Christodoulou [2], and treated by several authors [3][4][5][6][7][8][9][10][11][12][13][14][15]. As is usual in the treatment of isolated systems, all these works consider asymptotically flat spacetimes.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, L. Bieri and D. Garfinkle showed [11] that these are two different effects. For memory, see also the following works by Braginsky and Grishchuk [17], Braginsky and Thorne [18], Blanchet and Damour [14], Frauendiener [38], Wiseman and Will [76], and more recently Bieri, Chen, and S.-T. Yau [8], [9], Bieri and Garfinkle [10], [11], Tolish and Wald [73], Flanagan and Nichols [35], [36], and Favata [33]. We refer to these articles for further references.…”
Section: 2mentioning
confidence: 99%